EVALUASI KUALITAS KERIPIK BUAH NANGKA DENGAN METODE SIX SIGMA - Sucipto Sucipto; Ismi Ardiyati; Usman Effendi (Universitas Andalas, 2018)
Jackfruit is one of tropical fruit that is widespread in the world. Jackfruit fruit had a seasonal charachteristic and very perishable, so it needed to be further processed. One of the fruit chips producers in Malang SJ produced defects in jackfruit chips that were broken 74.5% of all defects types in 2014. Six Sigma method can be applied to evaluate the quality of jackfruit chips. This study aimed to evaluate the quality of jackfruit chips with Six Sigma - Define, Measure, Analyze, Improve (DMAI) so that it was known the Sigma of production, the main factors causing the defect, the priority proposed improvement, and the alternative using of jackfruit. The result of quality evaluation obtained by Sigma of production is 2.05. Factors that cause broken of jackfruit chips were machine, material, human, and methods. Priority improvements were made by resetting rotation speed of spinner according to the standard, completed the spinner’s standard operational procedure (SOP) and selecting the right jackfruit. Jackfruit from Malang can be an alternative raw material because it produces more whole jackfruit chips.